Participatory theme elicitation: open card sorting for user led qualitative data analysis. Issue 2 (4th March 2022) - Best, Paul; Badham, Jennifer; McConnell, Tracey; Hunter, Ruth F
ABSTRACT: Participatory Theme Elicitation (PTE) is a new approach to increasing user-involvement in qualitative data analysis. In this five-step method, participants independently identify themes in the data using open card sorting, and are supported in their development of a set of themes that reflect all participant views. We describe and evaluate PTE with a case study, where nine lay researchers identified five core themes in qualitative data from an online intervention with depressed adults. Total participation time was approximately 6 hours. Evaluation data revealed high levels of satisfaction with the PTE process and the themes generated. The strong commitment to public engagement in social science research and limited guidance on methods for effective participatory analysis of qualitative data highlight the value and growing need for robust standardised approaches such as PTE.